Thyroid Hormones, T3 and T4, in the Brain - Schroeder, Amy C.; Privalsky, Martin L. (Frontiers in Endocrinology, 2014)
Thyroid hormones (THs) are essential for fetal and postnatal nervous system development and also play an important role in the maintenance of adult brain function. Of the two major thyroid hormones, T4 (3,5,3',5' tetra-iodo-L-thyronine) is classically viewed as an pro-hormone that must be converted to T3 (3,5,3' tri-iodo-L-thyronine) via tissue-level deiodinases for biological activity. THs primarily mediate their effects by binding to thyroid hormone receptor (TR) isoforms, predominantly TRα1 and TRβ1, which are expressed in different tissues and exhibit distinctive roles in endocrinology. Notably the ability to respond to T4 and to T3 differs for the two TR isoforms, with TRα1 generally more responsive to T4 than is TRβ1. TRα1 is also the most abundantly expressed TR isoform in the brain, encompassing 70-80% of all TR expression in this tissue. Conversion of T4 into T3 via deiodinase 2 in astrocytes has been classically viewed as critical for generating local T3 for neurons. However, deiodinase-deficient mice do not exhibit obvious defectives in brain development or function. Considering that TRα1 is well established as the predominant isoform in brain, and that TRα1 responds to both T3 and T4, we suggest T4 may play a more active role in brain physiology than has been previously accepted.